(untitled) (De Rebus Antiquis, 2021)
Taking as starting point the appreciation of Constant about the Athenian freedom like herald of modern liberal spirit, the following article makes a series of statements in relation to more specific ways of understanding that appreciation. In this sense, a key figure analyzed here is Solon of Athens (630 – c.”‰560 BC), to whom Constant arrived through Plutarch. The complete argument of the article is set in the Introduction.